Prevalence and risk factor of piriformis syndrome among online motorcycle taxis in Denpasar, Bali - Ni Made Wira Tania Astarini; Nila Wahyuni; Ari Wibawa; Agung Wiwiek Indrayani; I Putu Eka Widyadharma (Department of Anatomy, Medical Faculty, Universitas Udayana, Bali-Indonesia, 2020)
Objective: the purpose of this study was to find out the prevalence and risk factors of Piriformis syndrome in online motorcycle taxis in Denpasar Methods: This study was an observational study with cross-sectional study design. The total sample was 87 respondents, and the sampling method used a purposive sampling technique. Results: research result showed prevalence and risk factor of piriformis syndrome based on risk factors for work duration: the prevalence of Piriformis syndrome in respondents with a duration of work of more than 8 hours was 48 (55.2%) respondents while 39 respondents (44.8%) in respondents with a duration of work of fewer than 8 hours. Based on the habit of putting a wallet in the back pocket, there were 33 (37.9%) respondents who had that habit while respondents without that habit had 54 respondents (62.1%). Conclusion: in a conclusion work duration, the habit of putting a wallet in the back pocket becomes a risk factor for piriformis syndrome in an online taxi driver.